Perbedaan Nilai Kapasitas Vital Paksa pada Laki-Laki antara Pekerja Pabrik dan Bukan Pekerja Pabrik Di Sukoharjo - Kisman, Andi Irawan, dr. Sri Wahyu Basuki, M.Kes (2017)
Background: Value of Forced Vital Capacity is a component of lung dynamic volume describing lung function of an individual. Factory workers who have been exposed to dangerous materials such as dust and occupational hazardous materials can experience reduction of FVC value because of irritation in respiratory tract by the dust, so that airway obstruction occurs. Purpose: Purpose of the research was to know difference of forced vital capacity (FVC) values between male factory workers and male non-factory workers. Method: The research was observational-analytic one by using cross-sectional approach. Sample was taken by using purposive sampling technique. The sample was 62 respondents consisting of 31 male factory workers and 31 male non-factory workers who were meeting restriction criteria. Spirometer was used as measurement tool. The data was analyzed by using unpaired T-test. Results: Data analysis found that the mean value of FVC for male factory workers was 2.16 L and the mean value of FVC for male non-factory workers was 2.69 L. Thus, FVC of male factory workers and FVC of non-factory workers were different with p-value < 0.001. Conclusion: A significant difference of forced vital capacity (FVC) values between male factory workers and male non-factory workers was found.